Optimization of thermal properties of palm fiber and nanofillers reinforced epoxy nanocomposite - Suresh Thirupathi; Venkatachalam Gopalan; Elango Mallichetty (Scientific Reports)
Abstract In recent times, the growing economic concerns and the rising cost of synthetic fibers have shifted focus to natural fiber reinforced composites, which are evident in the current literature. It is important to understand the thermal properties of these materials for functional applications. This study investigates the thermal conductivity of epoxy composites reinforced with sodium hydroxide (NaOH)-treated palm fruit fiber, a rarely used natural resource, with the addition of nanofillers, multi-walled carbon nanotubes, hexagonal boron nitride (h-BN), and aluminium oxide (Al2O3) used at 1 wt.%. The hand layup method is used to fabricate nanocomposites with varying palm fiber content (1–5 wt.%) with mesh size (75–225 µm) and nanofiller. The prepared nanocomposite samples are measured for thermal conductivity. SEM analysis manifests that alkali treatment increases the surface morphology of fiber as cleansed from impurities, which in turn increases bonding with the epoxy matrix at the interface. RSM was used to optimize these parameters, specifically the Box-Behnken Design (BBD) of RSM, with ANOVA analysis using Design-Expert 13 software to generate a strong regression model. The results demonstrate a maximum thermal conductivity of 1.54 W/m·K with 1 wt.% of palm fiber, 75 µm mesh size and 1% h-BN. This research emphasizes the promise of epoxy composites based on palm fibers for applications in thermal management in areas such as electronic devices, and circuit boards while contributing to the development of novel and efficient material solutions.